Ecclesiastical Justice in the Diocese of Coimbra in the 16th Century: Organization, Structure and Jurisdiction - Gouveia, Jaime Ricardo (2018)
A reorganization of the organisms of justice in the diocese of Coimbra during the first half of the 16th century culminated in the publication of a Regiment of the Episcopal Court (Auditório), ordered by the bishop of Coimbra D. João Soares in 1547. The prescripts issued by the Council of Trent, intended to reinforce vigilance and regulate and purify the Christian behaviour of prelates, also resulted in a reform of the ecclesiastical judicial system. It was in this context that D. Afonso de Castelo Branco ordered a new Regiment of the Episcopal Court which was published on 3 March, 1592. This normative corpus was central to the operation of the diocese, the rationalization of administrative procedures and the praxis of daily government, and is an invaluable source in the study of episcopal tribunals. By examining the profiles, competences and functions of the various agents who worked there, we will analyze the organization and internal structure of the tribunal of Coimbra.